Foreign aid effectiveness case study of Haiti - Hudáková, Miriama (2014)
My master's thesis deals with a form of soft power and foreign policy, the development aid. In the three chapters I provide an analysis of the potential impacts of such financial flows in the particular case of Haiti. This country has become an exemplar of the fact that even billions of dollars do not have to contribute to improving the economic and living conditions, on the contrary, aid in combination with incorrectly set policies can become an instrument of destruction. Using econometric models and policy analysis I examine the impact of official development assistance on the political, economic, environmental and social sector. At the end of the work I list recommendations for the future, which could contribute to improving the situation.